2021
DOI: 10.1177/1526602821996722
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Remodeling After Custom-Made Candy-Plug for Distal False Lumen Occlusion in Aortic Dissection

Abstract: Purpose: To report a single-center experience with the use of a custom-made Candy-Plug (CP) for distal false-lumen (FL) occlusion in subacute and chronic aortic dissection (AD). Materials and Methods: A retrospective single-center analysis was conducted on consecutive patients with subacute and chronic AD who were treated with a custom-made CP for distal FL occlusion using 3 design generations (CP I to CP III) from October 2013 to September 2019. Results: A custom-made CP was used in 57 patients. Of these, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…6,7 Since the first description of this technique, improvements have been developed to the CP device to allow a better occlusion of the FL, avoiding persistent retrograde reperfusion, and limiting concerns about the possibility of narrowing the TL. 4,11 The first device was obtained with a back table modification of a 42 mm Zenith thoracic TX2 Pro-Form stent-graft (Cook Medical, Bloomington, Indiana). 1 After the initial proof of concept, the CP I was developed as a custom-made device, and feasibility studies reported good early outcomes with low morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7 Since the first description of this technique, improvements have been developed to the CP device to allow a better occlusion of the FL, avoiding persistent retrograde reperfusion, and limiting concerns about the possibility of narrowing the TL. 4,11 The first device was obtained with a back table modification of a 42 mm Zenith thoracic TX2 Pro-Form stent-graft (Cook Medical, Bloomington, Indiana). 1 After the initial proof of concept, the CP I was developed as a custom-made device, and feasibility studies reported good early outcomes with low morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported the feasibility of the CP III technique with low mortality and morbidity and a high rate of aortic remodeling. 4,7,15 Despite device improvements that allowed avoiding the need for central plug deployment steps and the increased conformability of the 3 nitinol stents to the false aortic wall with better occlusion rates, some possible technical pitfalls deserve further discussion. After implantation in the FL, the sleeve might remain in front of a FL originating reno-visceral arteries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations